MNEs entry strategies through a distance framework: A new perspective - Xanthippe Adamoglou; Dimitrios Kyrkilis (SPOUDAI - Journal of Economics and Business, 2020)
The aim of the paper is to conceptually reconcile entry-mode strategy with the CAGE distance framework, going beyond narrow country-level borders and turning its attention to firm-level analysis. This main objective is split into two complementary intentions: first, the transformation of CAGE to "CIGE" distance framework. And, second, the approach of "CIGE" through the reconciliation of the TCA and Institutional theory. The context of the present analysis is emerging markets, since such economies frame the emerging organizational arrangements, practices and structures within which firms operate. The basic argument of the paper is that entry strategies in emerging markets will be affected by both transaction and institutional considerations. The paper contributes to the existing literature by conceptualizing entry-mode choice via a pluralistic, in terms of distance, framework. It introduces institutional distance into CAGE and approaches institutional distance as a "reservoir" of different institutional aspects that take into account challenges related to different institutional voids caused by various intermediaries. It integrates the reconciliation of TCA and Institutional theory into a unified distance setting in order to create a genuine interactive and dynamic conceptual basis on which TCA and institutional theory can apply. Last, it presents conceptual and managerial implications that open up new avenues for future empirical research.
Keywords: L22; L220; L24; L240; 330; Entry Mode Strategies; CAGE; Transaction Cost Theory; Institutional Theory; Emerging economies